DIGITAL MARKETING PADA PELAKU USAHA PEMULA DI SMK AT TAUFIQIYAH - Pranata, Mohammad Firlie; Wijaya, Nur Qoudri; Septiani, Ria (Universitas Madura, 2023)
Sumenep is the easternmost city in Madura. Sumenep has natural wealth that has great potential to be used as a business area. Micro, small and medium enterprises (MSMEs) are expected to spearhead the economy in Sumenep district, plus the district has a program for a thousand entrepreneurs and a thousand tourism to introduce Sumenep Regency as the soul of Madura. Sumenep is home to the Wiraraja University campus which has a Faculty of Economics and Business with a Digital Business Study Program. This is a benchmark for instilling an entrepreneurial spirit from an early age.At – Taufiqiyah Vocational School, Sumenep Regency, located at Jl. Safari No. 035 Aengbaja Raja, Bluto sub-district, Sumenep Regency. This teaches students to instill an entrepreneurial spirit from an early age, but it is a shame that the school does not yet have a special department for business and marketing or digital business. At - Taufiqiyah Vocational School gradually has to follow the development of digital technology which has provided major and fundamental changes in various aspects of life as well as business organizations, a practical approach in managing changes in business organizations in the digital era so that the transformation carried out by planning and implementing strategies produces human resources who are better prepared to face change. This researcher found that students initially studied digital marketing autodidactically or on their own by trying to market using the social media they had, but this was not enough without intense training to increase students' knowledge and skills, such as by practicing advertising, product photos and strategies for marketing on social media so that students can finally enter the market or set up a shop in a market place, but this needs to be done because currently students are just trying without any clear training. Students are expected to be able to serve customers or customers in a friendly and open manner, be disciplined in their business and be able to do digital marketing well.